2014
DOI: 10.1308/003588414x13946184901605
|View full text |Cite
|
Sign up to set email alerts
|

A personal perspective on controversies in the surgical management of oesophageal cancer

Abstract: Significant disagreement and debate persist regarding several aspects of the optimal surgical management of oesophageal cancer. We address some of these issues based on our consecutive series of 165 patients undergoing oesophageal resection (reported in full elsewhere) and the available literature. The areas considered are controversial but we argue in favour of a 'traditional' two-stage open approach (Ivor-Lewis), leaving the pylorus alone, making no attempt to perform a radical lymphadenectomy and fashioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Intrathoracic anastomosis performed in mid-esophageal lesions is not free of the risk of cancer-positive resections margins (25). Certain studies have emphasized that R0 resection in particular has an impact on survival rate (26). None of the patients in the present study that underwent anastomosis on the neck after subtotal esophagectomy were positive for cancer within the resection margin.…”
Section: Discussionmentioning
confidence: 53%
“…Intrathoracic anastomosis performed in mid-esophageal lesions is not free of the risk of cancer-positive resections margins (25). Certain studies have emphasized that R0 resection in particular has an impact on survival rate (26). None of the patients in the present study that underwent anastomosis on the neck after subtotal esophagectomy were positive for cancer within the resection margin.…”
Section: Discussionmentioning
confidence: 53%
“…Rindani et al [35] found a stricture rate of 28% among patients in the THE group vs. 16% among patients in the TTE group and Liu et al found a stricture rate of 19.8% among patients in the THE group vs. 13.5% among patients in the TTE group [35]. Gastric conduit ischaemia with subsequent post-operative anastomotic leaks, stapled anastomosis, cardiovascular diseases and COAD were identified as risk factors [24,31,33,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Although the initial results were promising, with a comparable outcome to open resection, avoiding thoracotomy will further reduce pulmonary complications associated with an open approach, and better visual control allows favourable oncological quality of resection. However, there is still no convincing evidence that MIE is superior to open oesophagectomy [24].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, ESCA has a high rate of lymphatic metastasis, and whether MIE is beneficial to the prognosis and long-term survival of patients with advanced ESCA has not been confirmed; meanwhile, Markar et al 20 found that in some cases, the short-term outcome of MIE was worse compared with OE, so some scholars are currently doubtful whether MIE is superior to OE. 21,22 Therefore, the aim of this study is to compare the effects of MIE and OE on postoperative complications, wound infection and hospital stay in ESCA patients through meta-analysis, so as to provide a theoretical basis for the selection of the best surgical method for ESCA patients.…”
Section: Introductionmentioning
confidence: 99%